Solid waste recycling scenario of Rajshahi City, Bangladesh - Bari, Md Niamul; Alam, Md. Zahangir; Jamal, Parveen (2007)
Rajshahi city, the divisional headquarters of Bangladesh, generates between 300-350 tons of solid wastes every day. In order to protect the hazardous effects, this large quantity of wastes requires to be managed properly. Recycling of such wastes is a challenging task in the contemporary world, especially in developing countries. This study is carried out to project the scenario of solid waste recycling pattern of Rajshahi City by using a viable and cost effective waste management technique. A detailed empirical study has been conducted in railway station area (vodra) and stadium market to collect the information about recyclable materials in recycling shops. The information about the people involved has been collected by interviewing them (scavengers, street hawkers and shopkeepers of recyclable materials) at different levels. Different recyclable wastes generated by some industries are visited in order to collecting information about the industrial involvement in the recycling practice. About 4000 people were involved in recycling practice in the city that has a great impact on the socio-economic condition in the city. There are 35 industries and organizations in which recyclable wastes are used as raw materials and reusable materials. The study shows that the most recycled items are iron, plastic and glass. Almost 17% of the total generated solid wastes is recycled everyday in the city. Therefore, present study reveals that the recycling pattern of solid wastes in Rajshahi City which can give a feed back to the City Planner and Government for taking step to improve the present status.